Spectrophotometric Determination of Cr(III) and Pb(II) Using Their Complexes with 5, 11, 17, 23-Tetra[(2-ethyl acetoethoxyphenyl)(azo)phenyl]calix[4]arene. (23rd April 2015) - Van Tan, Le; Quang Hieu, Tran; Van Cuong, Nguyen
Abstract : New complexes of 5, 11, 17, 23-tetra[(2-ethyl acetoethoxyphenyl)(azo)phenyl]calix[4]arene (TEAC) with Pb(II) and Cr(III) were prepared in basic solution with a mixture of MeOH and H2 O as solvent. The ratio of TEAC and metal ion in complexes was found to be 1 : 1 under investigated condition. The complex formation constants (based on Benesi-Hildebrand method) for TEAC-Pb(II) and TEAC-Cr(III) were 4.03 × 10 4 and 1.2 × 10 4, respectively. Additionally, the molar extinction coefficients were 5 × 10 4 and 1.42 × 10 4 for TEAC-Pb(II) and TEAC-Cr(III), respectively. The H-Point Standard Addition Method (HPSAM) has been applied for simultaneous determination of complexes formation of Cr(III)/Pb(II) and TEAC with concentration from 2 : 1 to 1 : 20 (w/w). The proposed method was successfully utilized to invest lead and chromium contents in plating wastewater samples. The results for several analyzed samples were found to be in satisfied agreement with those acquired by using the inductively coupled plasma mass spectrometry (ICP-MS) technique.